2017
DOI: 10.1188/17.onf.384-392
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, Symptom Distress, Illness Appraisal, and Coping in Patients With Advanced-Stage Cancer Diagnoses Undergoing Chemotherapy Treatment

Abstract: Illness appraisal, coping style, and symptom distress are important targets for intervention. Optimism is a beneficial trait and should be included, along with coping style, in comprehensive nursing assessments of patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
(53 reference statements)
1
31
0
2
Order By: Relevance
“…In contrast, other studies have elected to focus on negatively valanced outcome indicators, such as depression, anxiety, anger, psychological distress, negative affectivity, and symptom distress or severity (Arnett et al, 2002; Barinkova and Mesarosova, 2013; Bartmann and Roberto, 1996; Ben-Zur et al, 2000; Bose et al, 2016). Finally, a substantial number of studies preferred to use, as outcomes, more stable personality characteristics such as optimism, hope, neuroticism, helplessness, resilience, self-efficacy, and self-concept (Lynch et al, 2001; Miller et al, 1996; Murberg et al, 2004; Peter et al, 2014; Shen et al, 2004; Strober, 2017; Sumpio et al, 2017; Tan-Kristanto and Kiropoulos, 2015; Tomberg et al, 2005; Trivedi et al, 2009). Research findings, however, have consistently demonstrated that both positively and negatively measured psychological constructs tap different conceptual domains, and are, therefore, largely independent in nature (Diener and Emmons, 1984; Watson et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, other studies have elected to focus on negatively valanced outcome indicators, such as depression, anxiety, anger, psychological distress, negative affectivity, and symptom distress or severity (Arnett et al, 2002; Barinkova and Mesarosova, 2013; Bartmann and Roberto, 1996; Ben-Zur et al, 2000; Bose et al, 2016). Finally, a substantial number of studies preferred to use, as outcomes, more stable personality characteristics such as optimism, hope, neuroticism, helplessness, resilience, self-efficacy, and self-concept (Lynch et al, 2001; Miller et al, 1996; Murberg et al, 2004; Peter et al, 2014; Shen et al, 2004; Strober, 2017; Sumpio et al, 2017; Tan-Kristanto and Kiropoulos, 2015; Tomberg et al, 2005; Trivedi et al, 2009). Research findings, however, have consistently demonstrated that both positively and negatively measured psychological constructs tap different conceptual domains, and are, therefore, largely independent in nature (Diener and Emmons, 1984; Watson et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Duration of medical condition since onset or diagnosis varies appreciably among the various studies reported in the literature (See Table 1). More specifically, whereas in some studies, findings were obtained from participants’ experiences that were reported only several days or weeks following CID onset or diagnosis (Barone and Waters, 2012; Bartmann and Roberto, 1996; Ben-Zur et al, 2001; Bigatti et al, 2012; Bose et al, 2016; Bryant et al, 2000; Buckelew et al, 1990; Hack and Degner, 1999; Kennedy et al, 2012; King et al, 1998; Lowe et al, 2000; Moore et al, 1994; Sumpio et al, 2017; Tan-Kristanto and Kiropoulos, 2015; Terry, 1992), other studies based their findings on coping efforts that were reported many months or even years and decades following the disabling experience (Falgares et al, 2019; Goretti et al, 2009; Grech et al, 2016; Lequerica et al, 2008; Pakenham and Stewart, 1997; Peter et al, 2014). Finally, in many studies, data were averaged across a wide range of years since onset or diagnosis, that spanned up to 25 years among heart patients (King et al, 1998), 35–52 years in people with MS (Lode et al, 2010; O’Brien, 1993; Pakenham, 1999), 37–40 years among SCI survivors (Elfstrom et al, 2005; Lequerica et al, 2008), and 8–30 years among TBI survivors (Moore et al, 1994; Rogan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal resources may also favour post-traumatic growth, leading to positive changes in, e.g., self-perception, interpersonal relations and the philosophy of life (Ogińska-Bulik, 2015). Patients receiving chemotherapy who were characterised by greater optimism and self-efficacy experienced fewer mood disturbances, were less avoidant, and appraised their disease more positively (Sumpio, Jeon, Northouse, & Knobf, 2017). Spanish research has explicitly demonstrated that hope, optimism, social support, being male and older were associated with a significantly lower risk of anxiety and depression in cancer patients (Jimenez-Fonseca et al, 2018).…”
Section: Flexibility In Coping and Its Importance In Functioning Durimentioning
confidence: 99%
“…Pacjenci poddani chemioterapii cechujący się większym optymizmem oraz poczuciem skuteczności doświadczali mniej zaburzeń nastroju, byli mniej unikający, mieli bardziej pozytywną ocenę swojej choroby [28]. Chorzy onkologicznie po zabiegu chirurgicznym szybciej wracali do zdrowia, gdy charakteryzowali się większym poczuciem skuteczności i otrzymywali więcej wsparcia społecznego [29].…”
Section: Rola Zasobów Psychicznych: Prężności I Nadziei W Funkcjonowunclassified